In utero transmission and tissue distribution of chronic wasting disease-associated prions in free-ranging Rocky Mountain elk - Selariu, Anca (J Gen Virol, 2015)
The presence of disease-associated prions in tissues and bodily fluids of chronic wasting disease (CWD)-infected cervids has received much investigation, yet little is known about mother-to-offspring transmission of CWD. Our previous work demonstrated that mother-to-offspring transmission is efficient in an experimental setting. To address the question of relevance in a naturally exposed free-ranging population, we assessed maternal and fetal tissues derived from 19 elk dam–calf pairs collected from free-ranging Rocky Mountain elk from north-central Colorado, a known CWD endemic region. Conventional immunohistochemistry identified three of 19 CWD-positive dams, whereas a more sensitive assay [serial protein misfolding cyclic amplification (sPMCA)] detected CWD prion seeding activity (PrP(CWD)) in 15 of 19 dams. PrP(CWD) distribution in tissues was widespread, and included the central nervous system (CNS), lymphoreticular system, and reproductive, secretory, excretory and adipose tissues. Interestingly, five of 15 sPMCA-positive dams showed no evidence of PrP(CWD) in either CNS or lymphoreticular system, sites typically assessed in diagnosing CWD. Analysis of fetal tissues harvested from the 15 sPMCA-positive dams revealed PrP(CWD) in 80 % of fetuses (12 of 15), regardless of gestational stage. These findings demonstrated that PrP(CWD) is more abundant in peripheral tissues of CWD-exposed elk than current diagnostic methods suggest, and that transmission of prions from mother to offspring may contribute to the efficient transmission of CWD in naturally exposed cervid populations.